2009
DOI: 10.1103/physrevb.80.235202
|View full text |Cite
|
Sign up to set email alerts
|

Electron-hole recombination in disordered organic semiconductors: Validity of the Langevin formula

Abstract: Accurate modeling of electron-hole recombination in organic light-emitting diodes ͑OLEDs͒ is essential for developing a complete description of their functioning. Traditionally, the recombination rate is described by the Langevin formula, with a proportionality factor equal to the sum of the electron and hole mobilities. In the disordered organic semiconductors used in OLEDs these mobilities have been shown to depend strongly on the carrier densities and on the electric field. Moreover, the energetic disorder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 27 publications
4
69
0
Order By: Relevance
“…As mentioned in the introduction, the size and sign of the correlation between the on-site HOMO and LUMO energies have an important impact on the exciton formation rate [23]. Figure 8 shows in a scatter plot for all molecular sites in microscopic ab initio calculations for the three considered materials the values of E LUMO ≡ E LUMO − E LUMO versus E HOMO ≡ E HOMO − E HOMO , where E LUMO and E HOMO are the average LUMO and HOMO energies.…”
Section: Homo−lumo Energy Correlationsmentioning
confidence: 95%
See 3 more Smart Citations
“…As mentioned in the introduction, the size and sign of the correlation between the on-site HOMO and LUMO energies have an important impact on the exciton formation rate [23]. Figure 8 shows in a scatter plot for all molecular sites in microscopic ab initio calculations for the three considered materials the values of E LUMO ≡ E LUMO − E LUMO versus E HOMO ≡ E HOMO − E HOMO , where E LUMO and E HOMO are the average LUMO and HOMO energies.…”
Section: Homo−lumo Energy Correlationsmentioning
confidence: 95%
“…In the case of positive HOMO-LUMO energy correlation (negative correlation between electron and hole energies in the terminology used in Ref. [23]), the probability that electrons and holes are trapped at different sites is larger than in the case of negative HOMO-LUMO energy correlation (positive correlation between electron and holes energies). This leads to a lower exciton formation rate for positive than for negative HOMO-LUMO energy correlation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that we have recently shown that in order to properly describe electron-hole recombination in double-carrier devices, it is also necessary to take into account the effects of short-range interactions. 38 If these interactions are included in the mobilities in a double-carrier situation, an accurate description of the recombination rate is found when these mobilities are used in the conventional Langevin expression for this rate. 38 It would therefore be highly desirable to develop a systematic theory for including short-range Coulomb effects on charge-carrier mobilities in disordered organic semiconductors.…”
Section: Effects Of Short-range Coulomb Interactions On the Threementioning
confidence: 99%